Quillaja saponaria bark saponin protects Wistar rats against ferrous sulphate-induced oxidative and inflammatory liver damage - Mustafa Ahmed Abdel-Reheim; Basim Anwar Shehata Messiha; Ali Ahmed Abo-Saif (Taylor & Francis Group, 2017)
Context: Saponins from different sources are historically reported in Chinese medicine to possess many beneficial effects. However, insufficient experimental data are available regarding the hepatoprotective potential of Quillaja bark saponin. Objective: The protective effect of Quillaja saponaria Molina (Quillajaceae) bark triterpenoid saponin against iron-induced hepatotoxicity is compared to the standard N-acetylcysteine in adult male Wistar rats. Materials and methods: Animals were divided into (six) groups, namely a normal control, an N-acetylcysteine control (300 mg/kg/day, p.o., 10 days), a saponin control (100 mg/kg/day, p.o., for 10 days), a hepatotoxicity control (two doses of ferrous sulphate, 30 mg/kg/day each, i.p., on 9th and 10th day), an N-acetylcysteine plus ferrous sulphate (standard treatment) and a saponin plus ferrous sulphate (test treatment) group. Hepatocyte integrity loss markers (serum ALT, AST, ALP, GGT and LDH), oxidative stress markers (hepatic MDA, GSH and NOx), dyslipidaemic markers (serum TC and TG) and hepatocyte functioning markers (serum bilirubin and albumin) were assessed. Results: Quillaja bark saponin decreased iron-induced elevation of ALT (reaching 57% of hepatotoxicity control), AST (66%), ALP (76%), GGT (60%), LDH (54%), MDA (65%), NOx (77%), TC (70%), TG (54%), and total (54%), direct (54%) and indirect (54%) bilirubin, coupled with increased GSH (219%) and albumin (159%) levels. Histopathological study strongly supported biochemical estimations, while immunohistochemical study showed marked effect on eNOS and iNOS expression. Conclusions: Quillaja bark saponin has a good hepatoprotective effect. Amelioration of oxidative stress and suppression of NOS expression, with resultant maintenance of hepatocyte integrity and functioning, may explain this beneficial effect.